2017
DOI: 10.1007/s10549-017-4540-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of flap fixation techniques in reducing seroma formation and its sequelae after mastectomy

Abstract: The scientific body of evidence favoring flap fixation after mastectomy is convincing. Mechanical flap fixation seems to reduce seroma formation and seroma aspiration after mastectomy. There are, however, no well-powered randomized controlled trials evaluating all aspects of seroma formation and its sequelae. Further research should elucidate whether flap fixation using sutures or tissue glue is superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Many factors are held responsible (surgical technique, instruments used for dissection, obliterating the dead space, use of drains) causing seroma formation. The key to reducing seroma formation and its sequelae seems to lie in reduction of the dead space [ 9 ]. Previous retrospective studies have proven that reduction of the dead space after mastectomy is beneficial in seroma formation and that it furthermore reduces complications associated with seroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors are held responsible (surgical technique, instruments used for dissection, obliterating the dead space, use of drains) causing seroma formation. The key to reducing seroma formation and its sequelae seems to lie in reduction of the dead space [ 9 ]. Previous retrospective studies have proven that reduction of the dead space after mastectomy is beneficial in seroma formation and that it furthermore reduces complications associated with seroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to reduce the dead space of the cavity. Flap fixation using sutures (quilting) after mastectomy to reduce dead space has been found by some to be beneficial, leading to a decreased volume of seroma . More recently, surgical adhesives such as fibrin sealants have proved effective in promoting hemostasis and tissue sealing .…”
Section: Introductionmentioning
confidence: 99%
“…Flap fixation using sutures (quilting) after mastectomy to reduce dead space has been found by some to be beneficial, leading to a decreased volume of seroma. 5 More recently, surgical adhesives such as fibrin sealants have proved effective in promoting hemostasis and tissue sealing. 6 Animal models have shown that the use of fibrin sealants reduced seroma formation, [7][8][9] and in human studies, fibrin sealants reduced the amount of drainage following mastectomy when used with a drain.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been proposed in order to reduce seroma formation, such as external compression dressing [37], drainage placement [38][39][40][41], usage of fibrin glue [42,43], flap fixation and obliteration of the dead space [44], unfortunately with inconsistent results.…”
Section: Discussionmentioning
confidence: 99%